2009
DOI: 10.5172/jamh.8.2.135
|View full text |Cite
|
Sign up to set email alerts
|

Two way approaches to Indigenous mental health training: Brief training in brief interventions

Abstract: This study aimed to train health care professionals in a mental health assessment and care plan package designed for Aboriginal clients and carers and to evaluate the training and the package. The package has been developed over two years of consultation and encourages a collaborative, culturally appropriate approach to mental health assessment and care planning using motivational counselling techniques and relapse prevention strategies. Seventeen workshops were delivered in a range of settings to 261 service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…AIMhi promotes access to mental health treatment for Indigenous people through health promotion and education tools grounded in cross-cultural understandings of mental health and illness. 9 11 AIMhi motivational care planning (MCP) combines problem solving therapy and motivational interviewing, in a ‘low-intensity’ treatment that differs from established approaches by utilizing a holistic, strengths-based approach with pictorial tools. 10,12 MCP involves four steps: discussion about family support, exploration of strengths, and stressors, followed by goal setting.…”
mentioning
confidence: 99%
“…AIMhi promotes access to mental health treatment for Indigenous people through health promotion and education tools grounded in cross-cultural understandings of mental health and illness. 9 11 AIMhi motivational care planning (MCP) combines problem solving therapy and motivational interviewing, in a ‘low-intensity’ treatment that differs from established approaches by utilizing a holistic, strengths-based approach with pictorial tools. 10,12 MCP involves four steps: discussion about family support, exploration of strengths, and stressors, followed by goal setting.…”
mentioning
confidence: 99%
“…The Aboriginal and Islander Mental Health Initiative (AIMhi) in the Northern Territory has conducted foundational work over two decades developing culturally responsive wellbeing tools through grass roots involvement with First Nations people and guidance by First Nations Expert Reference Groups [ 43 45 ] These tools take into account the ‘whole of life’ view of First Nations people where cultural, spiritual and social wellbeing are integral to health, and are informed by study findings that First Nations people in the NT prefer holistic messages using storytelling, language, art work and key cultural informants to convey health information. The AIMhi goal to promote health literacy and accessible mental health treatment led to development and testing of a new brief therapy ‘Motivational Care Planning’ [ 46 ]. Designed to address mental illness and related comorbidity through a holistic and empowering approach, the ‘Stay Strong Plan’ immediately attracted interest from colleagues in substance misuse, chronic conditions and palliative care [ 44 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…‘Motivational care planning’ (MCP) combines problem solving therapy and motivational interviewing, to create a ‘low-intensity’ treatment that differs from established approaches by utilising a holistic, strengths-based approach with pictorial tools [10, 12]. It was evaluated in one of the first successful NHMRC-funded RCTs assessing mental health interventions in a remote Indigenous context, with further qualitative studies and evaluations confirming acceptability and feasibility [9, 11, 13, 14]. The RCT showed that the MCP intervention resulted in significant improvements in well-being, life skills, and alcohol dependence among Indigenous clients with chronic mental illness, with changes sustained over 18 months [9].…”
Section: Introductionmentioning
confidence: 99%